Endoscopic Vein Harvesting – How Do We Do It? - Veiga Oliveira, Paulo (2024)
The saphenous vein graft (SVG) remains the most used conduit as a second graft in Coronary Artery Bypass Grafting (CABG).1 Traditionally, surgeons harvest SVG with an open approach, making a long incision along the medial part of the leg or thigh. This procedure can potentially result in important complications, such as delayed wound healing, postoperative pain and infection.2 Thus, less invasive techniques for vessel harvesting have grown in popularity. Endoscopic vein harvesting (EVH) is a minimally invasive harvesting procedure, which only requires a short incision, leading to less wound complications and a faster return to normal daily activities. This article intends to describe how we do EVH technique in our centre, from the preparation of the patient to the postoperative period and share some tips and tricks from our experience.